Tale of a Comatose Female with Polyuria - Abtahir, Taha; Rifat, Islam; Sadia, Rimi; Abdur , Rahim; Rafiqul, Islam (Bangladesh Journal of Medicine, 2024)
A 28-year-old non-diabetic, hypertensive house wife got admitted due to fall from standing followed by gradually developing irrelevant talking. After 5 days, she became disoriented followed by loss of consciousness. On query, attendant gave history of gradually increasing, intermittent, cramping lower abdominal pain for last 2 months. On examination, patient was comatose, body built below average, anemic, BP 70/40 mm (Hg), pulse- 60 beats/ min, GCS: E2V1M2= 5/15, Planter response bilaterally extensor, tenderness over the hypogastric region. Initially our impression was septic encephalopathy , so we followed 1 hour “Sepsis Bundle” sending blood culture, urine culture & serum procalcitonin & routine investigations. At the 1ST day following admission, patient’s urine output was 7000 ml in last 24 hours followed by 3 episodes of generalized tonic clonic seizure & urinary & fecal incontinence. In the meantime, investigations ensured sepsis as well as electrolyte imbalance. CSF study revealed CNS Tuberculosis. So, we started anti tubercular medication. At 5TH day following admission, Patient regained her consciousness. At 7TH day, patient passed 10 liter of urine in a day. We ensured strict intake output chart. 24 hours urinary electrolytes were indicating urinary loss. We opted for urine for beta-2-microglobulin and it came out positive. So, after long 23 days of recovery from polyuria, we discharged the patient with the final diagnosis of Disseminated Tuberculosis (CNS TB &Tubulo-interstitial Nephritis) with Electrolyte imbalance (Hyponatremia, Hypokalemia, Hypochloremia & Hypomagnesemia) and Scabies with Erosio Interdigitalis Blastomycetica with Xerosis. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 176